Sanskrit language and names of Costa Rican businesses - Morales Harley, Roberto (2020)
The paper studies a corpus of thirty Costa Rican businesses with names of Sanskrit etymology and classifies them according to three criteria: geographical location, type of business, and theme in Sanskrit. Also, it analyses, for each word, the meaning, the etymology, and the relation to the business. Finally, it gathers some figures, which reveal the incidence of the Sanskrit language in the Costa Rican commercial context.